2019
DOI: 10.1167/tvst.8.3.36
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Semiautomated Kinetic Perimetry (SKP) and Goldmann Kinetic Perimetry in Children and Adults With Retinal Dystrophies

Abstract: Purpose To investigate the precision of visual fields (VFs) from semiautomated kinetic perimetry (SKP) on Octopus 900 perimeters, for children and adults with inherited retinal degenerations (IRDs). Goldmann manual kinetic perimetry has long been used in the diagnosis and follow-up of these patients, but SKP is becoming increasingly common. Octopus VFs (OVFs) and Goldmann VFs (GVFs) were both mapped on two occasions. Methods Nineteen females and 10 males with IRDs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…26 However, these changes should be interpreted with caution, as greater variability in visual field measurements is predicted in patients with more advanced stages of BCVA-or visual field-based impairment. [36][37][38] This is evidently demonstrated in our cohort as 4 severe visually impaired patients showed improvements up to 90% in visual fields areas at follow-up, in absence of intervention. Goldmann kinetic perimetry assumes stable and foveal fixation, which is not always the case in patients with severe RP such as in the current study.…”
Section: Discussionmentioning
confidence: 74%
“…26 However, these changes should be interpreted with caution, as greater variability in visual field measurements is predicted in patients with more advanced stages of BCVA-or visual field-based impairment. [36][37][38] This is evidently demonstrated in our cohort as 4 severe visually impaired patients showed improvements up to 90% in visual fields areas at follow-up, in absence of intervention. Goldmann kinetic perimetry assumes stable and foveal fixation, which is not always the case in patients with severe RP such as in the current study.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have shown that the hyper-AF ring correlates with the presence of the EZ band and demarcates the transition between healthy and affected retina [2,22,23]. The constriction of this hyper-AF ring in RP indicates disease progression, whereas, conversely, the expansion of the hyper-AF ring in CRD patients suggests disease progression [2,24].…”
Section: Discussionmentioning
confidence: 96%
“…[28] The reliability of the GVF is however highly operator dependent, and prone to erroneous results from variable target speeds, particularly for small and dim targets. [29,30] The original Goldmann perimeter is no longer produced, and has been replaced by semi-automated kinetic perimetry (SKP) devices with standardization of target velocity and test pattern. The SKP Octopus 900 (Haag Streit AG, Koeniz, Switzerland) has shown strong agreement with the GVF, and is considered a viable alternative to the GVF in clinical trials and for clinical care.…”
Section: Low-luminance Visual Acuity Colour Vision and Contrast Sensmentioning
confidence: 99%
“…The SKP Octopus 900 (Haag Streit AG, Koeniz, Switzerland) has shown strong agreement with the GVF, and is considered a viable alternative to the GVF in clinical trials and for clinical care. [30,31] Studies testing the quantitative analysis of OCT as a structural measure for disease progression have shown that perception of the Goldmann I4e isopter correlates with retinal areas showing an intact inner segment ellipsoid zone. [32] The usefulness of the Goldmann visual field as a clinical trial outcome measure however is limited by its high test-retest variability and its operator dependence.…”
Section: Low-luminance Visual Acuity Colour Vision and Contrast Sensmentioning
confidence: 99%